A Sampler from the New Historical Atlas of Maine: Religion in Maine - Hatlen, Burton; Smith, Joshua; Lodge, Peter; Hermann, Michael (Maine Policy Review, 2002)
This article offers an example of work-in-progress on a significant project to develop an historical atlas of Maine. Although an article depicting religious settlement in Maine may seem far removed from the policy analyses typically featured in the journal, religious participation is a fundamental aspect of civic engagement in the United States. Thus, we feature here a glimpse of Maine’s religious heritage. We also present Maine Policy Review’s first full color pullout, which is intended to give readers a visual as well as textual portrait of religious settlement in the Kennebec Valley and Portland through the first half of the nineteenth century.